Ensino de ciências na educação de jovens e adultos: aproximações com a perspectiva freireana - SILVA, Marcelo Eduardo Silva da (Universidade Federal do Pará, 2024)
This work was guided by the reality of Youth and Adult Education (EJA), where the reproduction of social inequalities is crystallized, where two actors stand out, teacher and student. The question that motivates the research is to know how activities based on the curricular proposal of the Freirean Thematic Approach - ATF can contribute to the teaching and learning of science in this modality. To do so, we used as theoretical reference the contributions of Paulo Freire and Demétrio Delizoicov, called Generative Themes and Freirean Thematic Approach respectively. Both made it possible to achieve the general objective, which was to investigate the contributions of activities based on ATF for science teaching and learning, in the 2nd stage of EJA, in a peasant school in the municipality of S J. de Pirabas / PA. The main results found, pointed out that the aforementioned approach is perfectly feasible, as it proved capable of producing: relevant knowledge, motivated students to continue learning and mitigated evasion. In addition to demonstrating the importance of praxis as a tool that provides not only a progression of year / stage, but the transition from ingenuity to criticality. The aforementioned experience provided the construction of an Educational Product in the form of a Guidance Guide for Developing Activities Based on ATF, aimed at EJA classes. In which a rupture with the conceptions of teaching of traditionalist nature is presented, because it uses social contradictions linked to the knowledge of science contained in BNCC as an increase of the school curriculum.